Christianity and womanhood : evolving roles and responsibilities - Rogers, Wyatt M. (Praeger, 2002)
The status of women in Christianity has waxed and waned countless times over the centuries. During the early history of Israel, several women had roles as national and spiritual leaders. Later came the age of patriarchs with its male dominance and relegation of women to subservient status. Despite the male-dominated religious system of the time, Rogers sees Christ as elevating the status of women in various ways. Today, however, he examines how Christianity has failed to meet its responsibilities to advance the roles of women. Rogers explores the current and historical status and roles of women as providers and recipients of Christian ministries. The burgeoning needs of women in society are examined along with the obstacles and opportunities for women as vocational ministers of the Gospel. Primarily of interest to pastors/ministers, seminary professors, and lay leaders in churches, Bible study teachers, and members of churches and Bible study group/classes.